2009
DOI: 10.1177/0022034509350037
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Factors for Periodontitis in a Japanese Population

Abstract: Genetic variants at multiple loci have been shown to be associated with susceptibility to periodontitis. To better assess the genetic risk factors for periodontitis, we performed a case-control study in 319 Japanese individuals with periodontitis (172 aggressive and 147 chronic disease) and 303 race-matched healthy control individuals. Thirty-five functional gene polymorphisms that had been previously associated with immune responses were genotyped. For all gene polymorphisms tested, no significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…For example, Kornman firstly reported in 1997 that chronic periodontitis was related to interleukin (IL)-1 (IL-1 ) polymorphism [1] . Following this report, many other studies attempted to elucidate the associations of chronic periodontitis (CP) with polymorphisms in other genes, including IL-6 and Vitamin D receptor ( VDR ) [2, 3]. These results suggested that unregulated production of inflammatory cytokines would be a risk factor for chronic periodontitis.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Kornman firstly reported in 1997 that chronic periodontitis was related to interleukin (IL)-1 (IL-1 ) polymorphism [1] . Following this report, many other studies attempted to elucidate the associations of chronic periodontitis (CP) with polymorphisms in other genes, including IL-6 and Vitamin D receptor ( VDR ) [2, 3]. These results suggested that unregulated production of inflammatory cytokines would be a risk factor for chronic periodontitis.…”
Section: Introductionmentioning
confidence: 98%
“…However, there have been few studies on the relationship between AgP and polymorphisms, in the TLR genes. Although one study demonstrated a significant association between CP and a polymorphism in TLR4 [13], another study could not replicate the significant association [3]. On the other hand, no association was observed with a TLR2 polymorphism, Agg753Gln, in a German population [14], and a study in Japanese subjects also showed no association of CP with the TLR2 polymorphisms, Arg677Trp and Arg753Gln [13].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the meta-analysis was to evaluate the precise association between five 29 widely-evaluated polymorphisms (CD14 À260C/T (rs2569190), Toll-like receptor (TLR) 2 2408G/A 30 (rs5743708), TLR4 896A/G (rs4986790), TLR4 1196C/T (rs4986791), mannose-binding lectin (MBL) codon 31 54 (rs1800450)) within the PRRs and susceptibility to either chronic (CP) or aggressive periodontitis 32 (AgP). Overall, no significant association was found for the PRRs polymorphisms with either CP or AgP.…”
mentioning
confidence: 99%
“…The prevalence of this form of periodontitis significantly varies between countries and depends on one's ethnicity 2,3,4 . The factors that may lead to aggressive periodontitis are numerous: above all, poor dental hygiene which leads to a build-up of oral bacteria forming a dental film 5,6 . Another significant factor causing this form of periodontitis is a compromised immune system.…”
Section: Introductionmentioning
confidence: 99%